Correlation between the surface electronic structure and CO-oxidation activity of Pt alloys. Issue 7 (1st October 2014) - Abe, Hideki; Yoshikawa, Hideki; Umezawa, Naoto; Xu, Ya; Saravanan, Govindachetty; Ramesh, Gubbala V.; Tanabe, Toyokazu; Kodiyath, Rajesh; Ueda, Shigenori; Sekido, Nobuaki; Yamabe-Mitarai, Yoko; Shimoda, Masahiko; et al.
Abstract : The CO-oxidation activity of Pt and Pt alloys, Pt3T (T = Ti, Hf, Ta, Pt), shows a volcano-type dependence on the d-band center of the catalysts. Abstract : The surface electronic structure and CO-oxidation activity of Pt and Pt alloys, Pt3 T (T = Ti, Hf, Ta, Pt), were investigated. At temperatures below 538 K, the CO-oxidation activities of Pt and Pt3 T increased in the order Pt < Pt3 Ti < Pt3 hHf < Pt3 Ta. The center-of-gravity of the Pt d-band (the d-band center) of Pt and Pt3 T was theoretically calculated to follow the trend Pt3 Ti < Pt3 Ta < Pt3 Hf < Pt. The CO-oxidation activity showed a volcano-type dependence on the d-band center, where Pt3 Ta exhibited a maximum in activity. Theoretical calculations demonstrated that the adsorption energy of CO on the catalyst surface monotonically decreases with the lowering of the d-band center because of diminished hybridization of the surface d-band and the lowest-unoccupied molecular orbital (LUMO) of CO. The observed volcano-type correlation between the d-band center and the CO oxidation activity is rationalized in terms of the CO adsorption energy, which counterbalances the surface coverage by CO and the rate of CO oxidation.